2018
DOI: 10.1016/j.jsxm.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Effects of Intracavernosal Phenylephrine for the Treatment of Ischemic Priapism

Abstract: Aim We sought to evaluate whether the administration of phenylephrine (PE) at concentrations higher than those described in guidelines resulted in any significant changes in vital signs or impacted outcomes. Methods After receiving institutional review board approval, we retrospectively reviewed the charts of patients presenting to our emergency department between May 1, 2014, and August 15, 2016, using International Classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This highlights the importance of understanding regional differences in patient populations. For instance, in a recent study looking at the hemodynamic effects of phenylephrine in the treatment of ischemic priapism, a group identified drug induced priapism to be the leading cause of priapism, of which a majority of that was secondary to penile injection therapy (6). For our institution, erectogenic medications accounted for 24% of patients presenting with priapism, but sickle cell anemia accounted for the majority of the visits.…”
Section: Limitationsmentioning
confidence: 79%
See 3 more Smart Citations
“…This highlights the importance of understanding regional differences in patient populations. For instance, in a recent study looking at the hemodynamic effects of phenylephrine in the treatment of ischemic priapism, a group identified drug induced priapism to be the leading cause of priapism, of which a majority of that was secondary to penile injection therapy (6). For our institution, erectogenic medications accounted for 24% of patients presenting with priapism, but sickle cell anemia accounted for the majority of the visits.…”
Section: Limitationsmentioning
confidence: 79%
“…A large majority of visits were the result of recurrent ischemic priapism (93% of EM managed patients and 69% of the urology consults). Recurrent ischemic priapism is not unique in our patient population, as other patient level studies have shown up to 50% of the priapism patients having multiple visits for priapism (6,19). Recurrent ischemic priapism is described as painful and multiple transient episodes of priapism that can progress into an acute ischemic episode.…”
Section: Management Of Recurrent Ischemic Priapismmentioning
confidence: 85%
See 2 more Smart Citations